MILLIY XARAKTERDAGI FRAZEOLOGIZMLARNING SHAKLLANISH MANBALARI - Xujaniyazov, E.; Sultanova, N. (SCIENCE and SOCIETY, 2017)
The article is devoted to the issues of expressing the national character of the people in phraseology. The author studies the connection of phraseological units with the life of people and it is given the explanation commentary to concrete phraseological units.
Keywords: phraseology; national character; Persian -Tadjik language; lexeme; to form; unity of meanings; mobility; subject; anthroponym; component